Komitmen Organisasi Staf Jurnal Indonesia berdasarkan Komunikasi, Kepemimpinan, dan Etika Kerja - Faraz; Setiadi, Anggi Arif Fudin; Khoerunnisa, Elfrida; Nastiyar, Firdaus Algim (Jurnal Komunikasi, 2023)
Increasing the organizational commitment of employees or staff is one way to increase organizational performance so that it remains competitive and resilient. The aim of this research is to determine the relationship between servant leadership and interpersonal communication and Islamic work ethics as mediators with the organizational commitment of journal managers. Quantitative methods were used with (online) questionnaires distributed to universities in Indonesia. The novelty of this research is using measuring instruments for interpersonal communication and organizational commitment that are different from several previous studies. The research results show that all independent variables are significantly related to organizational commitment factors, except interpersonal communication. Interpersonal communication has no significant relationship with organizational commitment (P=0.822), but when mediated by Islamic work ethics it has a significant relationship with organizational commitment (P=0.001). This means that Islamic work ethics become a full mediator of interpersonal communication relationships and organizational commitment. The influence of leadership factors on organizational commitment is very strong (P=0.001). On the other hand, when mediated by Islamic work ethics, the influence decreases (P=0.004).